Effektivnost' vrascatel'nych nagruzok pri soversenstvovanii ravnovesija v sportivnych edinoborstvach - Nazarenko, L. D.; Cechalin, I. V. (Teorija i Praktika fiziceskoj Kul'tury, 2004)
The offered methods of stimulation of the developments and improvements to stability of the body beside taekwondo with the use of specific and not specific rotate loads. The development of the balance on its main variety and manifestations allows to take into account all the forming elements this motor coordination.